O trabalho e a aprendizagem da profissão docente no estágio curricular supervisionado - Nobre, Robério Ferreira (2020)
The supervised internship is characterized as a field of knowledge for the teacher, a space for training and teaching practice, favoring the professional constitution. In this study, it seeks to understand the practice of the internship in the Licenciatura courses in Biological Sciences, Letters and Mathematics at the Regional University of Cariri - URCA, at the Campos Sales campus; verify the work and learning of the teaching profession in the supervised curricular internship, taking into account the subjects inserted directly in this period: the supervising teachers of the internship, the trainees who concluded the last internship and are in the phase of completion of the course and the governing teachers of the internship field schools. Theoretical contributions supported contributions by Pimenta and Lima (2008), Barreiro and Gebran (2006), Coelho, Silveira, Bezerra (2016), Didone (2007), Ghedin, Oliveira and Almeida, (2015), Passini, (2015), Piconez, (1991), Zabalza (2014), Castro (2013) among others. And in the legal apparatus under the internship: Opinion CNE / CP 27/2001, Resolution CNE / CP 1 and 9/2002, Resolution no. 2/2015, among others. It was based on the qualitative approach, working with the subjects participating in the internship period: professor supervising internship, conducting professor of the school field of internship and intern in phase of completion of course. The methodology for data collection and analysis was implemented through two questionnaire instruments with the subjects involved and analysis of the interns' internship reports. Here teaching is built in the internship period, through the experiences and permanent mediations and interventions of teacher educators, becoming the basic axis in professional construction, the measure that makes it possible to build a teacher and [re] signify educational and articulate the knowledge present and built in this period. In this study, he identified internship conceptions as the application of theory in practice, and the time to live in the professional space overcame the challenge of structuring the schedules between academics, professionals and interns. Unfortunately, he realized a great fear of teaching present in the academic interns and a great rupture in institutional relations. Thus, the internship is the space for the construction, restructuring and reframing of the knowledge needed by the teaching professional.